Facial expression recognition: convolutional attentional masking network and ensemble approach - Kowsar, Ibna; Zaman, Mashﬁq Shahriar; Sakib, Md. Fahmidur Rahman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.